2021
DOI: 10.1097/ede.0000000000001338
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-based Propensity Scores for Confounding Control in Comparative Effectiveness Research

Abstract: Background: Due to the non-randomized nature of real-world data, prognostic factors need to be balanced, which is often done by propensity scores (PSs). This study aimed to investigate whether autoencoders, which are unsupervised deep learning architectures, might be leveraged to compute PS. Methods:We selected patient-level data of 128,368 first-line treated cancer patients from the Flatiron Health EHR-derived de-identified database. We trained an autoencoder architecture to learn a lowerdimensional patient r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…Lots of recent research efforts have been devoted to developing complex deep learning-based models for propensity score based modeling 7,[40][41][42][43] In this paper, after emulating hundreds of thousands of trials from two large-scale RWD warehouses, we found that one LSTM-PS 7 , which is a representative deep learning based PS method, did not outperform LR-PS. Our study also highlighted the importance of model selection and we proposed our own strategy under which we demonstrated LR-PS outperformed gradient boosting tree-based PS models and deep multi-layer peceptron-based PS models as well in terms of balancing performance and the number of generated repurposing hypotheses.…”
Section: Discussionmentioning
confidence: 89%
“…Lots of recent research efforts have been devoted to developing complex deep learning-based models for propensity score based modeling 7,[40][41][42][43] In this paper, after emulating hundreds of thousands of trials from two large-scale RWD warehouses, we found that one LSTM-PS 7 , which is a representative deep learning based PS method, did not outperform LR-PS. Our study also highlighted the importance of model selection and we proposed our own strategy under which we demonstrated LR-PS outperformed gradient boosting tree-based PS models and deep multi-layer peceptron-based PS models as well in terms of balancing performance and the number of generated repurposing hypotheses.…”
Section: Discussionmentioning
confidence: 89%
“…26 The use of neural networks for extracting confounder information by modeling complex coding patterns is promising but examples are limited. 27,28 2.1 | Challenges in generating features for proxy adjustment from electronic health records An important limitation of current high-dimensional proxy confounder adjustment approaches is that they can only use structured electronic healthcare information. However, much of the essential confounder information, such as patient-reported symptoms, severity, stage and prognosis of the disease, and functional status, is frequently recorded in free-text notes or reports in electronic health records (EHRs) that are substantially underutilized for confounding adjustment.…”
Section: Generating Features For Proxy Confounder Adjustmentmentioning
confidence: 99%
“…For example, recent work has proposed using neural networks to model a patient's full course of care to consider temporal sequences of a specific course of treatment 26 . The use of neural networks for extracting confounder information by modeling complex coding patterns is promising but examples are limited 27,28 …”
Section: Generating Features For Proxy Confounder Adjustmentmentioning
confidence: 99%
“…CT scans [6], histopathology slides [7], genomics [8], transcriptomics [9], [10], and most recently, integrated approaches with various data types [11], [12]. In general, studies using DL show excellent predictive performance, providing hope for successful translation into clinical practice [13], [14]. However, prediction accuracy in DL comes with potential pitfalls which need to be overcome before wider adoption can be eventuated [15].…”
Section: Introductionmentioning
confidence: 99%